Electrical, Piezoresistive and Electromagnetic Properties of Graphene Reinforced Cement Composites: A Review - Shengchang Mu; Jianguang Yue; Yu Wang; Chuang Feng (Nanomaterials, 2021)
Due to their excellent combination of mechanical and physical properties, graphene and its derivatives as reinforcements have been drawing tremendous attention to the development of high-performance and multifunctional cement-based composites. This paper is mainly focused on reviewing existing studies on the three material properties (electrical, piezoresistive and electromagnetic) correlated to the multifunction of graphene reinforced cement composite materials (GRCCMs). Graphene fillers have demonstrated better reinforcing effects on the three material properties involved when compared to the other fillers, such as carbon fiber (CF), carbon nanotube (CNT) and glass fiber (GF). This can be attributed to the large specific surface area of graphene fillers, leading to improved hydration process, microstructures and interactions between the fillers and the cement matrix in the composites. Therefore, studies on using some widely adopted methods/techniques to characterize and investigate the hydration and microstructures of GRCCMs are reviewed and discussed. Since the types of graphene fillers and cement matrices and the preparation methods affect the filler dispersion and material properties, studies on these aspects are also briefly summarized and discussed. Based on the review, some challenges and research gaps for future research are identified. This review is envisaged to provide a comprehensive literature review and more insightful perspectives for research on developing multifunctional GRCCMs.